Seasonal foraging gaps and floral resource enhancement opportunities for Apis cerana in a tropical conservation forest - INDRI WULANDARI; TEGUH HUSODO; JOKO KUSMORO; ERRI NOVIAR MEGANTARA; SYA SYA SHANIDA; CIKA ASTI AMALIA; HANANI ROSY AZZAHRA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Wulandari I, Husodo T, Kusmoro J, Megantara EN, Shanida SS, Amalia CA, Azzahra HR. 2025. Seasonal foraging gaps and floral resource enhancement opportunities for Apis cerana in a tropical conservation forest. Biodiversitas 26: 4201-4219. The Asiatic honey bee (Apis cerana) relies on pollen and nectar from flowering plants to sustain its colonies. When floral resources are limited, colonies may abscond, which threatens the livelihoods of beekeepers in the Ir. H. Djuanda Forest Park, West Java, Indonesia. Ensuring continuous forage availability is therefore essential for sustainable A. cerana management. This study aimed to (i) identify the food sources of A. cerana, both are based on pollen and flowering records, (ii) document the flowering period, and (iii) recommendations for forage enrichment in Ir. H. Djuanda Forest Park. Pollen trapping, quadrat, and direct observation were conducted within a 1 km radius of apiaries in Batu Garok, Deer Enclosure, and Maribaya. A total of 279 species were documented, consisting of 71 pollen plants and 252 flowering plants. The dominant floral families recorded were Asteraceae, Fabaceae, and Euphorbiaceae. The flowering plants diversity peaked between December and May, with 188-216 species (approximately 70-85% of the annual total) recorded during this period. In contrast, a critical floral gap occurred between June and November, when only 50-118 species (around 20-50% of the annual total) were in bloom. This seasonal gap restricts foraging opportunities and increases the risk of colony absconding. To mitigate this, 30 year-round flowering species are recommended for enrichment planting. Among the recorded species, red calliandra (Calliandra calothyrsus) and Mexican sunflower (Tithonia diversifolia) were dominant year-round forage plants, consistently supplied pollen and nectar, although both are invasive species. Non-invasive year-round species are also recommended to enrich forage availability during the gap months; among them are billygoat weed (Ageratum conyzoides) and hairy beggarticks (Bidens pilosa). These results highlight the value of implementing targeted habitat enrichment to help bridge seasonal gaps in floral resources. Such efforts can contribute to greater colony stability, support higher honey yields, and enhance pollination services within tropical conservation forests.